Does Deposit Insurance Increase Banking System Stability? - Demirguc-Kunt, Asli.; Detragiache, Enrica (Washington, D.C. : International Monetary Fund, 2000)
This study analyzes panel data for 61 countries during 1980-97 and concludes that explicit deposit insurance tends to be detrimental to bank stability, the more so where bank interest rates are deregulated and the institutional environment is weak. Also, the adverse impact of deposit insurance on bank stability tends to be stronger when the coverage offered to depositors is extensive, when the scheme is funded, and when it is run by the government rather than by the private sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet